2016
DOI: 10.1111/resp.12765
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and health of adults with cystic fibrosis

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/resp.12719/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…According to Menetrey et al (2021) , it was shown that Stenotrophomonas maltophilia (SM) is an emerging pathogen that shares important pathophysiological features with CF pathogens and that SM possesses a large number of adaptive strategies to persist in CF patients. In terms of exercise and health, Williams (2016) found that cystic fibrosis ( CF ) patients who exercised for more than 30 min per day had fewer hospitalizations and improved lung function after 12 months compared to CF patients who exercised for less than 30 min per day. Kalamara et al (2021) also suggested that daily exercise can improve aerobic capacity and slow down the decline of lung function in CF patients, and a combination of aerobic and anaerobic training may be the best training approach for CF patients.…”
Section: Methodsmentioning
confidence: 99%
“…According to Menetrey et al (2021) , it was shown that Stenotrophomonas maltophilia (SM) is an emerging pathogen that shares important pathophysiological features with CF pathogens and that SM possesses a large number of adaptive strategies to persist in CF patients. In terms of exercise and health, Williams (2016) found that cystic fibrosis ( CF ) patients who exercised for more than 30 min per day had fewer hospitalizations and improved lung function after 12 months compared to CF patients who exercised for less than 30 min per day. Kalamara et al (2021) also suggested that daily exercise can improve aerobic capacity and slow down the decline of lung function in CF patients, and a combination of aerobic and anaerobic training may be the best training approach for CF patients.…”
Section: Methodsmentioning
confidence: 99%
“…The important findings from the present study were discussed by Williams in an editorial. 74 Exercise was a theme that was found in both the CF and the paediatric papers this year. A scientific letter from a group in Finland reported that exercise is associated with an increase in nasal patency in healthy children as well as children with atopic asthma and children with sensitization but not asthma.…”
Section: Claire E Wainwrightmentioning
confidence: 99%